2021
DOI: 10.3390/ijerph18020643
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Speed Profiles Based on Age and Sex Differences in Young Basketball Players

Abstract: Team sports are in continuous evolution, and physical performance is acquiring greater importance in the game. The assessment of physical fitness is the most reliable method for knowing if the athlete’s physical fitness is appropriate. Therefore, the objectives of this research were to identify profiles of physical-physiological demands with different specific tests of physical fitness related to the maximum strength of the lower body and speed. Moreover, some differences based on the sex and age of the player… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…Regarding physical fitness, the results of this study showed that elite male U-14 basketball players had superior jump heights (i.e., CMJ and DJ), linear speed (i.e., 5, 10, and 20 m-sprint times), COD speed (i.e., Lane Agility Drill and 505 COD tests), and RCOD speed (i.e., RCODAtotal) than female players. These results coincide with those reported in U-14 Spanish national basketball players revealing that male players (n = 33) possess superior lower-body power (i.e., abalakov jump and multi-jump test) and repeated-sprint capacity (i.e., repeat sprint ability test) compared to U-14 female players (n = 12) (Mancha-Triguero et al, 2021). This finding is supported with previous literature since sex differences in athletic performances start to increase around the age associated with the onset of puberty in males (12-13 years) (Handelsman, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding physical fitness, the results of this study showed that elite male U-14 basketball players had superior jump heights (i.e., CMJ and DJ), linear speed (i.e., 5, 10, and 20 m-sprint times), COD speed (i.e., Lane Agility Drill and 505 COD tests), and RCOD speed (i.e., RCODAtotal) than female players. These results coincide with those reported in U-14 Spanish national basketball players revealing that male players (n = 33) possess superior lower-body power (i.e., abalakov jump and multi-jump test) and repeated-sprint capacity (i.e., repeat sprint ability test) compared to U-14 female players (n = 12) (Mancha-Triguero et al, 2021). This finding is supported with previous literature since sex differences in athletic performances start to increase around the age associated with the onset of puberty in males (12-13 years) (Handelsman, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, only one study has compared physical fitness attributes in basketball players under 14 years of age (U-14) according to sex. Specifically, Mancha-Triguero et al (2021) observed that U-14 male basketball players who participated in the Spanish national championship performed better in single (male: 32.6 ± 2.6 cm; female: 25.5 ± 4.0 cm) and repeated (male: 26.4 ± 5.8 cm; female: 20.7 ± 4.3 cm) jumping tests while their U-14 female counterparts had better repeated-sprint ability (male: 14.1 ± 1.1 s; female: 13.8 ± 0.6 s). Given the limited evidence base to draw from, future studies on this topic seem necessary to facilitate the training process in basketball players during early adolescence for optimal progression into and across elite basketball academies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The order of tests was realized following a previous validated protocol [18] relation with the maturity development [12]. In this sense, higher values in male players were found in different capacities/abilities with such as aerobic capacity (related to the body size and age) [13], speed (related to the type II-B muscular fibers), strength (higher size of muscular belly), or agility (related to Q-angle and hip abduction) [11].…”
Section: Design and Proceduresmentioning
confidence: 99%
“…and physical parameters (strength, power, aerobic, and anaerobic capacity, etc.) [10,11], being the physical capacity the most variable aspect throughout a season [6]. It could be influenced by different contextual factors such as sex, age, and competitive level [3,4].…”
Section: Introductionmentioning
confidence: 99%